Electrodeposition preparation of a cauliflower-like Sb–SnO2 electrode from DMSO solution for electrochemical dye decolorization. Issue 53 (16th May 2016) - Duan, Ying; Chen, Ye; Wen, Qing; Duan, Tigang
Abstract : Ti/Sb–SnO2 electrode prepared in DMSO solution exhibits a distinct cauliflower-like structure, and has the significantly enhanced service lifetime and electrochemical dye decolorization activity. Abstract : We have developed a simple and effective way to fabricate Ti/Sb–SnO2 electrodes by electrodeposition from a dimethyl sulfoxide solution. The electrode surface exhibits a distinct cauliflower-like structure with a small grain size. Its electrochemical properties have been evaluated by electrochemical impedance spectroscopy and accelerated service life tests; furthermore, the results were compared with those obtained for an electrode prepared from aqueous solution. The DMSO-prepared electrode has low charge transfer resistance (22.71 vs. 107.60 Ω) and high stability (59.3 vs. 2.8 h). Moreover, its ability to electrochemically decolorize methyl orange and rhodamine B is greatly improved.